DESIGN OF EARTH TUBE HEAT ECHANGER FOR BATTERY PACK LITHIUM ION COOLING SYSTEM - Sangaji, Romi
One type of electrical energy storage that is quite good is to use Lithium Ion batteries because it has a high energy density and a longer life cycle compared to other batteries in general. With various advantages possessed, Lithium Ion batteries have a disadvantage in high temperature sensitivity. The heat released in battery usage will increase the temperature which will cause a decrease in performance on the battery, especially in reducing capacity in each life-cycle. Therefore, a cooling system is needed to keep the temperature of the battery low and even. A cooling system that can be used is earth tube cooling or a pipe heat exchanger system that buried in the ground. In this final project the system has been able to produce cooling air on 26.720C by flowing environmental air with a mass flow rate on 15.4 g/s which has the highest temperature on 31.450C into the ground through an iron galvanized pipe along 10m at a depth of 3m from the ground. The use of this cooling system of Lithium Ion batteries pack has been proven in simulations that can reduce the battery temperature from a maximum temperature of 400C to have an average temperature of 30.120C. This system has also been able to keep the battery temperature evenly, which can be seen from the standard deviation value of the measurement points on each battery reach 0.3.